Computational insights into novel inhibitors: virtual screening of small molecules against human carbonic anhydrase II - Arunachalam, Sermarajan; M. M., Balamurali; Gnanasekaran, Ramachandran (Frontiers in Chemistry, 2025)
Carbonic anhydrases, zinc-based metalloproteins, facilitate the reversible conversion of CO2 into carbonic acid when transported through blood vessels and subsequently regulate the physiological pH. In humans, this enzyme has been the therapeutic target for numerous diseases, as its abnormal regulation leads to a variety of disorders. The regulatory mechanism of this enzyme includes targeting catalytic Zn2+ ions as well as the residues that significantly regulate the protein’s structure and stability. With the available data on numerous sulfonamides, sulfamates, sulfamides, and non-sulfamide-derived inhibitors, in this study, a library of sulfonamide, extended aromatic sulfonamide, and non-sulfonamide derivatives was screened using a fragment-based drug discovery approach. Virtual screening was performed with molecular docking (DOCK 6 and Schrödinger GLIDE), rescored using MM-GBSA, and validated over 100-ns molecular dynamics simulations. Pharmacophore models were developed to identify key interaction features, while pharmacokinetic profiles were evaluated to assess their drug-likeness. Compounds S8 (sulfonamide) and S15–S16 (non-sulfonamides) emerged as promising inhibitors, showing strong Zn2+ coordination and stable binding to residues His93, Leu196, Thr197, and Thr198 that favor pharmacokinetic properties. The results provide atomistic insights into carbonic anhydrase II (CAII) inhibition and identify potential leads for further experimental validation.